Parents’ Uptake and Willingness towards Recommended Vaccinations for Their Children with Underlying Chronic Medical Conditions in Italy - Giorgia Della Polla; Grazia Miraglia del Giudice; Mario Postiglione; Italo Francesco Angelillo (Vaccines, 2023)
This cross-sectional survey was conducted to investigate the willingness and uptake of recommended vaccinations against influenza, meningococcal B and ACWY, pneumococcal, rotavirus and the influencing factors among 565 parents of children aged 6 months to 5 years with chronic medical conditions in Italy. Only 34.9% of the sample received all vaccinations. Parents whose selected child was vaccinated against the five diseases were those who had received recommendations from physicians, who did not believe that children should get fewer vaccinations at the same time, those whose child was aged 2–3 and 4–5 years compared to 6 months–1 year, and those who acquired information from physicians. Only 17.9% were willing to vaccinate their child. Parents with a university degree, those who acquired information from physicians, and those whose child had a more recent diagnosis were more likely to be willing to vaccinate their child. Parents who believed that children should get fewer vaccines at the same time, those without a university degree, and those who did not acquire information from physicians were more likely to not have vaccinated their child because they were concerned about vaccines’ side effects. Public health policymakers should provide efforts to promote the uptake for an adequate protection of this high-risk group.